Structural and functional properties of indica rice starch as influenced by late-stage nitrogen fertilization. Issue 1 (1st January 2021) - Teng, Bin; Xi, Min; Du, Shiyun; Zhou, Yongjin; Zhang, Ying; Zhang, Yuexiong; Luo, Zhixiang; Wu, Wenge
ABSTRACT: Late-stage nitrogen (N) fertilization is an important crop management for improving rice production and also affects the quality of rice, whereas information on the influence of late N on structural and functional properties of indica rice starch is lacking. In this study, effects of various N rates (0, 60, and 120 kg ha −1 referred to as N0, N60 and N120, respectively) on structural and functional properties of grain starches from two rice cultivars (OM052 and Chaoyou1000) were investigated. Comparison of different N treatments showed that late N application exhibited strong influence on starch properties, and the sensitivity to N application varied with rice genotypes. Compared to non N rate, higher input of N (N60 for OM052, and N120 for Chaoyou1000) significantly reduced apparent amylose content (AAC), relative crystallinity (RC), gelatinization enthalpy, swelling power, solubility and degree of hydrolysis, but significantly increased the proportion of short chains with degree of polymerization 6–12 in amylopectin and gelatinization onset temperature. Further comparison and principal component analyses revealed that the variations in the starch functional properties were due mainly to the changes in RC. The solubility was positively associated with AAC. The present results can provide important information for understanding the environmental regulation of starch biosynthesis in rice grain.